2018
DOI: 10.1039/c8cp04061c
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the enigma of ultrafast excited state relaxation in non-emissive aggregating conjugated polymers

Abstract: We investigate a class of non-emissive conjugated polymers with very short excited state lifetimes believed to undergo singlet fission and relaxation to mid-gap forbidden excited states. Poly(3-decylthieneylenvinylene) (P3DTV) and its heavy atom analog, poly(3-decylseleneylenvinylene) (P3DSV), are strongly aggregating conjugated polymers that experience large excited state displacements along multiple vibrational modes. We demonstrate this Franck-Condon vibrational activity effectively disperses excitation ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 50 publications
4
31
0
Order By: Relevance
“…The partially resolved progression interval represents the coalescence of many displaced vibrational modes ranging from ∼500 to 1600 cm −1 involving CC and CH stretching and bending motions with the full details of the Franck−Condon vibrational composition described in detail earlier. 33,35 Absorption contributions from amorphous (unaggregated) chains appear at higher energy (∼0.5 eV from the aggregate electronic origin), much weaker and devoid of a resolved structure. Similar to P3HT, contributions from aggregated or unaggregated chains may be discerned by decomposing their respective lineshapes from the overall absorption lineshape.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The partially resolved progression interval represents the coalescence of many displaced vibrational modes ranging from ∼500 to 1600 cm −1 involving CC and CH stretching and bending motions with the full details of the Franck−Condon vibrational composition described in detail earlier. 33,35 Absorption contributions from amorphous (unaggregated) chains appear at higher energy (∼0.5 eV from the aggregate electronic origin), much weaker and devoid of a resolved structure. Similar to P3HT, contributions from aggregated or unaggregated chains may be discerned by decomposing their respective lineshapes from the overall absorption lineshape.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Specifically, on-resonance excitation selects lesser ordered segments corresponding to either unaggregated chains or aggregates with low intra-chain order. 33,35 On the other hand, pre-resonant excitation conditions preferentially excite ordered, aggregated chain segments. 40 Asterisks denote new transitions arising from the presence of F 4 -TCNQ consistent with appreciable CT interactions, and their specific nature can be illuminated using variable excitation conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, Hu et al demonstrated that fluorescence emission could be restored by dispersing a PTV derivative in a solid inert host, causing aggregates to dissociate . Our group also recently observed rich Franck–Condon vibrational dynamics in aggregating PTVs, which promotes efficient nonradiative relaxation . While a comprehensive photophysical model describing the interdependence on molecular structure is still lacking, minimizing complications from aggregation and heterogeneity effects is essential to obtain unambiguous views of photophysical pathways .…”
mentioning
confidence: 98%
“…17 Our group also recently observed rich Franck− Condon vibrational dynamics in aggregating PTVs, which promotes efficient nonradiative relaxation. 18 on molecular structure is still lacking, minimizing complications from aggregation and heterogeneity effects is essential to obtain unambiguous views of photophysical pathways. 19 To this end, we demonstrate that dTV can serve as a model system for resolving vibrational contributions to intersystem crossing events in related molecules 20 and nonaggregating polymeric counterparts.…”
mentioning
confidence: 99%
“…This approximation has led to the development of useful models to explain and predict the excited-state reactivity of many chromophores and photochromes. [1][2][3][4][5] Recently, new interpretations of bifurcating transition states as well as molecules with large excited-state nuclear displacements have emerged to challenge the notion that a single reaction coordinate trajectory dominated by thermodynamics is capable of adequately describing complex excited-state reactivity. 4,6,7 The origin of these changes in interpretation is found in reactions where a transition state is located near a stationary point (location on the potential energy surface where energy gradients with respect to the nuclear position are small or zero) or a conical intersection thus enabling non-equilibrium molecular dynamics to dictate reaction outcomes over thermodynamics.…”
Section: Introductionmentioning
confidence: 99%